The Role of Molecular Systematics in Microbiological Research and Public Health: A Systematic Review - Ablola, Ferissa; Bautista, Ana Liza; Migalang, Gilden Maecah; Christa Jesusa Naval (Hasanuddin University, 2023)
The robust development of molecular biology and bioinformatics in recent years has given researchers strong tools for addressing long-standing issues in all branches of biology. The process of reconstructing phylogenetic relationships using molecular data is known as